(untitled) (Journal of Media studies, 2022)
Robotic process automation (RPA) has been widely adopted in manyindustries as a tool, which does repetitive actions in rule-based businessprocesses. Audit companies around the world are always on the way to makingprocesses more efficient with help of automation and RPA is not an exception.However, there are always two sides of the coin, and there are both benefits andlimitations of using RPA. Using RPA may be not efficient in somecircumstances, so it is important to understand in what cases using RPA willbring more advantages than disadvantages. The main purpose of this study is tounderstand the conditions under which adopting the Robotic ProcessAutomation Systems will influence the operational efficiency in the audit firmsin Kazakhstan. Because the main purpose of the study is to understand thechallenges and opportunities of applying RPA, a qualitative approach has beenselected. Data were collected through semi-structured interviews with fivespecialists in the audit sector. After transcribing the interview conversations, athematic analysis method resulted in 47 open-codes. In the analysis part wasdiscussed some tendencies, opportunities, and barriers of effectiveimplementation of RPA.